2014
DOI: 10.1039/c3ta15220k
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical nucleation and growth of Pd/PdCo core–shell nanoparticles with enhanced activity and durability as fuel cell catalyst

Abstract: Cyclic voltammetry curves of Pd NPs and Pd/PdCo core–shell NPs in 0.5 M HCOOH + 0.5 M H2SO4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…In the case of Cu and brass, two peaks appear in voltammograms which are associated to the Fe and Pd reduction [16]. The first peak in voltammograms is related to palladium diffusion-controlled region and next one to iron [33][34][35][36]. It is also found that for same overpotentials (Fig.…”
Section: Effect Of Substrate On Chemical Composition and Cathodic Curmentioning
confidence: 71%
“…In the case of Cu and brass, two peaks appear in voltammograms which are associated to the Fe and Pd reduction [16]. The first peak in voltammograms is related to palladium diffusion-controlled region and next one to iron [33][34][35][36]. It is also found that for same overpotentials (Fig.…”
Section: Effect Of Substrate On Chemical Composition and Cathodic Curmentioning
confidence: 71%
“…This led to the contraction of the Pd lattice along with the modication of the Pd electronic structure. [48][49][50][51] H 2 -TPR proles of PdM@Hal are given in Fig. 4b.…”
Section: Resultsmentioning
confidence: 99%
“…Pd-based catalysts are believed to be more suitable for FAO due to their lower adsorption of CO intermediates in catalyzing formic acid. [5][6][7] Nevertheless, the electrochemical activity and stability of Pd-based catalysts should be improved. Increasing the activity of Pd-based catalysts will lead to a low dosage of Pd in practical utilization.…”
Section: Introductionmentioning
confidence: 99%